الريادة التنموية لرأس المال البشري في ظل تحديات القرن الواحد والعشرين - عياش, زبير; قريوة, زينب; بوخالفة, رشيد (جامعة الوادي - University of Eloued, 2016)
تحظى الموارد البشرية بأهمية بالغة في التنظيمات الحديثة باعتبارها رأس مال فاعل وقادر على الإبداع والابتكار بالنظر إلى جملة المهارات ،والخبرات ،والمعرفة التي يتميز بها ، ويعد رأس المال البشري مصدرا لقيمة مضافة بالنسبة للتنظيمات الحديثة إذا ما توفرت له الشروط الهيكلية والزبونية، والظروف المناسبة لخلق مزايا تنافسية وتدعيمها في ظل مؤشرات الجودة والكفاءة والإبداع ،فكلما استجابت المخرجات التنظيمية لمعايير الجودة والكفاءة ومتطلبات البيئة الاقتصادية والاجتماعية كلما ساهمت في التنمية بصفة مباشرة . Abstract : Human resources are of paramount importance in modern organizations because they are a creativity and innovation actor, providing a number of skills, experience and knowledge that characterize human capital as a source of Added value for modern organizations if they had the right conditions to create competitive advantages and quality enhancement, subject to the existence of innovation indicators that meet regulatory standards of quality, efficiency and Requirements of the economic and social environment that enable organizations to contribute directly to development Keywords: sustainable development, human development, human capital.
مقال
Keywords: رأس المال البشري، التنمية البشرية، التنمية المستديمة ، الميزة التنافسية